Oxygen Saturation Behavior by Pulse Oximetry in Female Athletes: Breaking Myths - Pilar Martín-Escudero; Ana María Cabanas; Manuel Fuentes-Ferrer; Mercedes Galindo-Canales (Biosensors, 2021)
The myths surrounding women’s participation in sport have been reflected in respiratory physiology. This study aims to demonstrate that continuous monitoring of blood oxygen saturation during a maximal exercise test in female athletes is highly correlated with the determination of the second ventilatory threshold (<semantics>VT2</semantics>) or anaerobic threshold (AnT). The measurements were performed using a pulse oximeter during a maximum effort test on a treadmill on a population of 27 healthy female athletes. A common behavior of the oxygen saturation evolution during the incremental exercise test characterized by a decrease in saturation before the aerobic threshold (AeT) followed by a second significant drop was observed. Decreases in peripheral oxygen saturation during physical exertion have been related to the athlete’s physical fitness condition. However, this drop should not be a limiting factor in women’s physical performance. We found statistically significant correlations between the maximum oxygen uptake and the appearance of the ventilatory thresholds (<semantics>VT1</semantics> and <semantics>VT2</semantics>), the desaturation time, the total test time, and between the desaturation time and the <semantics>VT2</semantics>. We observed a relationship between the desaturation time and the <semantics>VT2</semantics> appearance. Indeed, a linear regression model between the desaturation time and the <semantics>VT2</semantics> appearance can predict <semantics>80%</semantics> of the values in our sample. Besides, we suggest that pulse oximetry is a simple, fairly accurate, and non-invasive technique for studying the physical condition of athletes who perform physical exertion.